Multinaming in the "Tríbadas" - Castilla del Pino, Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Tríbadas, by Miguel Espinosa, is subtitled Theologiae Tractatus. According to the autor it could also be titled A treatise of Naming. M. Espinosa takes on one of God's powers, that is, to give name to everything that exists. But the case in Tríbadas is that one same "object" -a person- is given many different names (that is the purpose of introducing the neologism "multinaming"). The reason for it is that sameness cannot be identified with identity. That same person is given different names because, by playing many relation functions with the being that names, is not identical to itself.
Keywords: Miguel Espinosa; Tríbadas; multinaming